Clinical aspects of binge eating disorder: A cross-sectional mixed-methods study of binge eating disorder experts' perspectives - Bray, Brenna; Sadowski, Adam; Bray, Chris; Bradley, Ryan; Zwickey, Heather (Frontiers in Psychiatry, 2023)
Research on binge eating disorder continues to evolve and advance our understanding of recurrent binge eating. This mixed-methods, cross-sectional survey aimed to collect information from experts in the field about clinical aspects of adult binge eating disorder pathology. Fourteen experts in binge eating disorder research and clinical care were identified based on receipt of relevant federal funding, PubMed-indexed publications, active practice in the field, leadership in relevant societies, and/or clinical and popular press distinction. Anonymously recorded semi-structured interviews were analyzed by ≥2 investigators using reflexive thematic analysis and quantification. Identified themes included: 1) obesity (100%); 2) intentional/voluntary or unintentional/involuntary food/eating restriction (100%); 3) negative affect, emotional dysregulation, and negative urgency (100%); 4) diagnostic heterogeneity and validity (71%); 5) paradigm shifts in understanding binge eating disorder (29%); and 6) research gaps/future directives (29%). Overall, experts call for a better understanding of the relationship between binge eating disorder and obesity, including a need for clarification around the extent to which the two health issues are separate vs. related/overlapping. Experts also commonly endorse food/eating restriction and emotion dysregulation as important components of binge eating disorder pathology, which aligns with two common models of binge eating disorder conceptualization (e.g., dietary restraint theory and emotion/affect regulation theory). A few experts spontaneously identified several paradigm shifts in our understanding of who can have an eating disorder (beyond the anorexi-centric “thin, White, affluent, cis-gendered neurotypical female” stereotype), and the various factors that can drive binge eating. Experts also identified several areas where classification issues may warrant future research. Overall, these results highlight the continual advancement of the field to better understand adult binge eating disorder as an autonomous eating disorder diagnosis.